HUMAN RIGHTS CONTENT OF THE DIGITAL TRANSFORMATION OF THE EUROPEAN UNION - Natalia V. Bocharova (Alfred Nobel University Journal of Law)
The article examines the fundamental foundations of the European approach to the regulation of digital transformation and the creation of an ideological and theoretical basis for the legal support of digitalization of society in the European Union. The concept of digital humanism, which is gaining more and more popularity, is analyzed and determines the content and direction of the EU policy on creating conditions for the digital transition. It states that digital humanism is a new field that examines the ethical, social, emotional, and political implications of digital technologies for human life. The conceptual design of the human rights approach to the regulation of digitalization in the EU is connected with the adoption of a number of documents, the analysis of which made it possible to determine the specifics of the approach to the regulation of the digital transition in the EU. It claims to be based on the desire to put people at the center of digital transformation, includes references to digital sovereignty, respect for fundamental rights, rule of law and democracy, inclusiveness, accessibility, equality, sustainability, sustainability, security, improved quality of life, accessibility of services, and respect for the rights and aspirations of everyone. It was emphasized that the European regulatory model of digital transformation, focused on a human rights approach, is supported by the world community and is being implemented on a global scale. This is due to the so-called Brussels effect, which consists in the spread of EU internal regulatory rules at the global level.